Which is the best method of sterilization of tumour bone for reimplantation? a biomechanical and histopathological study - Singh, Vivek Ajit; Nagalingam, J.; Saad, M.; Pailoor, J. (BMC, 2010)
Introduction: Sterilization and re-usage of tumour bone for reconstruction after tumour resection is now gaining popularity in the East. This recycle tumour bone needs to be sterilized in order to eradicate the tumour cells before re-implantation for limb salvage procedures. The effect of some of these treatments on the integrity and sterility of the bone after treatment has been published but there has yet been a direct comparison between the various methods of sterilization to determine the one method that gives the best tumour kill without compromising the bone's structural integrity. Method: This study was performed to evaluate the effect of several sterilization methods on the mechanical behavior of human cortical bone graft and histopathology evaluation of tumour bone samples after being processed with 4 different methods of sterilization. Fresh human cortical tumour bone is harvested from the diaphyseal region of the tumour bone were sterilized by autoclave (n = 10); boiling (n = 10); pasteurization (n = 10); and irradiation (n = 10). There were also 10 control specimens that did not receive any form of sterilization treatment. The biomechanical test conducted were stress to failure, modulus and strain to failure, which were determined from axial compression testing. Statistical analysis (ANOVA) was performed on these results. Significance level (alpha) and power (beta) were set to 0.05 and 0.90, respectively. Results: ANOVA analysis of 'failure stress', 'modulus' and 'strain to failure' demonstrated significant differences (p < 0.05) between treated cortical bone and untreated specimens under mechanical loading. 'Stress to failure' was significantly reduced in boiled, autoclaved and irradiated cortical bone samples (p < 0.05). 'Modulus' detected significant differences in the boiled, autoclaved and pasteurization specimens compared to controls (p < 0.05). 'Strain to failure' was reduced by irradiation (p < 0.05) but not by the other three methods of treatments. Histopathology study revealed no viable tumour cell in any of four types of treatment group compared to the untreated control group. Conclusions: Sterilization of cortical bone sample by pasteurization and to a lesser extent, irradiation does not significantly alter the mechanical properties when compared with untreated samples. Mechanical properties degrade with the use of high temperature for sterilization (boiling). All methods of sterilization gave rise to 100 percent tumour kill.